Pendapatan dan Peran Petani Subak Padanggalak di Objek Wisata Desa Budaya Kertalangu, Desa Kesiman Kertalangu, Kecamatan Denpasar Timur, Kota Denpasar - ANAK AGUNG MIRAH WIJAYANTI; WAYAN WINDIA; I DEWA GEDE AGUNG (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Income and Role of Subak Padanggalak Farmers in Tourism Objects of Kertalangu Cultural Village, Kesiman Kertalangu Village, East Denpasar District, Denpasar City The source of income of most farmers may come from several sources that is called as diversification of income. The role of farmers could be seen from the perspective of culture, namely culture as system of ideas or thought patterns, culture as system of activities, and culture as system of artifacts. The purpose of this study is to identify and understand the income and role of farmers in terms of culture in the development of Kertalangu Cultural Village Tourism Object. The study involves 54 farmers as respondents and was conducted in the second planting season between August and November 2018. The sample was determined using accidental sampling method. The research shows that the income of farmers in Subak Padanggalak with an average area of 0.26 ha of arable land is Rp. 4,695,377.78. Farming is efficient with an R/C ratio of 4.92, which means that for every Rp 100 costs incurred, Rp 4.92 income is received. The role of farmers is investigated from the aspect of culture that consist of three elements, namely mindset, social, and material. The aspect of mindset is reflected in decision-making processes related with the existence of new ideas or ideas regarding the development of attractions where farmers are also given the opportunity to provide advice or input. In relation to social aspects, the operation and maintenance of irrigation networks has become a routine activity agenda. In addition, farmers also become the object of tourism packages provided by the manager of the attractions. The role of farmers in material aspects can be seen from the maintenance of subak physical facilities, namely the maintenance of special plants that are planted for ceremonial service. In addition, farmers also organize and maintain empelan and other infrastructures which are used as sites to learn subak for students. Based on this research, Subak Padanggalak farmers should continue to improve agricultural skills in order to increase income and maintain the synergy of subak with tourism in order to harmonize the two sectors.